Hubungan Penggunaan User Interface Dengan Kemudahan Pemakaian Sistem Informasi Akademik (Siakad) Online Mahasiswa Uin Ar-Raniry Banda Aceh Tahun 2017 - AR, Khairan (PTE FTK UIN Ar-Raniry, 2018)
Measuring the ease of user interface using is often perceived as the second choice if it compared to the development of the software project. This view seems reasonable, because the project development becomes central issue that usually discussed when the institution decide to develop the systems. There are several considerations in developing the systems, which examine the needs of the users of the application. One of the consideration factors that the system should fulfil the need of user by assessing the perspective of user interface (UI) consumers from the students. However, the user interface measured in this study is SIAKAD online student of UIN Ar-Raniry Banda Aceh. Measuring the data variable need to assess was the relationship of UI usage with ease of UI SIAKAD online usage by UIN Ar-Raniry student Banda Aceh. To measure the level of relationship, the study used regression and correlation analysis approach, which the regression analysis is used to see the effect of free variables (x) UI usage on the dependent variable (y) ease of UI usage. Then, the correlation analysis is need to see the relationship between the two previously mentioned variables. From the results of simple linear regression analysis, there is a significant influence between free variables (x) UI usage, on the dependent variable (y) ease of UI usage, with R value of 0.732, R Square is 0,535 value, the overall value of R produced is greater than the value coefficient of 0,05. Therefore, the correlation analysis showed that there is a significant correlation between free variable (x) UI usage to the dependent variable (y) ease of UI usage, with significance value 0.000 less than 0.05.